(untitled) (Journal of Mathematical Study, 2023)
In this paper, we consider a system of set-valued nonlinear generalized variational inclusion problems (SNGVIP) in q-uniformly smooth Banach spaces. We define a class of H(·,·)-mixed mappings and its associated class of resolvent operators. Further, using proximal-point mapping method, we suggest an iterative algorithm for finding the solution of the system of set-valued nonlinear generalized variational inclusion problems. Furthermore, we discuss the convergence criteria of the sequences generated by the iterative algorithm.